Efetividade das estratégias não farmacológicas na atenção primária à saúde para o tratamento do Diabetes Mellitus tipo 2: revisão sistemática e meta-análise em rede - Leite, Renata Giacomini Occhiuto Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Introdução: Apesar do número crescente de medicamentos e das diversas diretrizes sobre o manejo do diabetes mellitus tipo 2 (DM2), inúmeros pacientes continuam com a doença descontrolada. Há uma diversidade de estratégias não farmacológicas disponíveis para o manejo do DM2, contudo, muitas delas ainda não foram comparadas diretamente a fim de determinar as mais eficazes. Objetivo: Este estudo avaliou os efeitos comparativos de estratégias não farmacológicas no manejo do DM2 na atenção primária ou em ambientes comunitários. Resultados: Depois de eliminar as duplicatas, as estratégias de busca resultaram em 4.314 estudos. A abordagem mais frequente foi o autogerenciamento e apoio ao diabetes (DSMES - Diabetes Self-Management Education and Support), seguido por educação para o auto-manejo do diabetes (DSME - Diabetes Self-Management Education), abordagens de suporte e educação para o auto-manejo do diabetes habilitadas por tecnologia (DSME_Tech - Diabetes Self-Management Education Technology), abordagens de suporte e educação para o auto- manejo do diabetes focadas em dieta de carboidratos (DSMES_CarbDiet), estratégias de suporte e educação para o auto-manejo do diabetes focadas em dieta do prato saudável (DSMES_PlateDiet), estratégias de suporte e educação para o auto-manejo do diabetes habilitadas por tecnologia (DSMES_Tech), estratégias de suporte e educação para o auto- manejo do diabetes via telefone (DSMES_Telephone), estratégias de suporte e educação para o auto-manejo do diabetes com suporte familiar (DSMES_FamilySup), dieta de substituição alimentar (FoodSubsDiet), coach de saúde (HC), coach de saúde e estratégias de suporte e educação para o auto-manejo do diabetes habilitadas por tecnologia (HC_DSMES_Tech), folhetos, benchmarking (Bench), terapia de exercício e nutrição (Nutri_Exercise), auto- monitorização da glicose sanguínea (SMBG) e Yoga. O comparador mais frequentemente utilizado foi cuidados habituais (UC - Usual Care) (92%). A suposição de consistência poderia ser aceita no nível geral de cada tratamento, (teste de inconsistência: chi2(8) = 14,511, p= 0,2048). Em relação às classificações relativas, o exercício e a terapia nutricional (uma combinação de uma prescrição de exercício e um plano alimentar) é a estratégia com maior probabilidade de ser pelo menos a terceira melhor (66,8%) em termos de redução da HbA1c, seguida pela dieta do prato saudável associada à DSMES (53,3%) e dieta de substituição alimentar (48,8%). No SUCRA, a área de superfície para exercício e terapia nutricional chega a quase 90%, confirmando novamente que é a melhor intervenção, seguida de substituição alimentar, dieta do prato saudável e DSMES, DSME e DSMES. Conclusão: Esta revisão encontrou 17 estratégias não farmacológicas no manejo do diabetes tipo 2 (DM2) na atenção primária, sendo a mais frequente a Educação e Suporte para o Automanejo do Diabetes (DSMES), e a terapia de exercícios e nutrição apresentou a maior probabilidade de ser a melhor em termos de redução da HbA1c.

Introduction: Despite the increasing number of drugs and various guidelines on the management of type 2 diabetes mellitus (T2DM), several patients continue with the disease uncontrolled. There are several non-pharmacological treatments available for managing T2DM, but various of them have never been compared directly to determine the best strategies. Objective: This study evaluated the comparative effects of non-pharmacological strategies in the management of T2DM in primary care or community settings. Methods: We have performed a systematic review and network meta-analysis (NMA) following the Cochrane collaboration and reported according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) Statement: We included randomized controlled trials if non-pharmacological strategies in the management of type 2 diabetes were applied in adult patients with T2DM in primary care. The primary outcome was glycemic control (glycated hemoglobin [HbA1c] [%]). We developed search strategies for Embase, Medline, Latin American and Caribbean Health Sciences Literature, Cochrane Central Register of Controlled Trials, Trip database, Scopus, Web of Science, Cumulative Index to Nursing and Allied Health Literature (CINAHL). Four reviewers assessed the studies for their eligibility and their risk of bias in pairs and independently. A NMA have been performed using Stata Statistical Software 17 (Stata Statistical Software: Release 18. College Station, TX, StataCorp LLC, USA). Results: After removing duplicates, the search strategies yielded 4314 studies. After a thorough evaluation of the references, 129 studies encompassing a total of 35975 individuals have been included in this review. Seventeen strategies were founded. The most frequent strategy was diabetes self-management and support (DSMES), followed by diabetes self- management education (DSME), technology enabled DSMES (DSME_Tech), diabetes self- management education and support strategies focused on carbohydrate diet (DSMES_CarbDiet), diabetes self-management education and support strategies focused on plate diet (DSMES_PlateDiet), technology-enabled diabetes self-management education and support strategies (DSMES_Tech), diabetes self-management education and support strategies via telephone (DSMES_Telephone), diabetes self-management education and support strategies with family support, (DSMES_FamilySup), food substitution diet (FoodSubsDiet), health coach (HC), health coach and technology-enabled diabetes self-management education and support strategies (HC_DSMES_Tech), leaflet, benchmarking (Bench), exercise and nutrition therapy (Nutri_Exercise), self-monitoring of blood glucose (SMBG) and Yoga. The most frequent comparator has been usual care (UC) (92%). The consistency assumption could be accepted at the overall level of each treatment (test for inconsistency: chi2(8) = 14.511, p = 0.2048). Regarding relative rankings, exercise and nutrition therapy (a combination of an exercise prescription and a dietary plan) is the strategy with the highest probability to be at least the third best (66.8%) in terms of HbA1c reduction, followed by plate diet associated with DSMES (53.3%), and food substitution diet (48.8%). In the SUCRA, the sur¬face area for exercise and nutrition therapy reaches almost 90%, confirming again that it is the best intervention, followed by food substitution, plate diet and DSMES, DSME and DSMES. Conclusion: This review has founded 17 non-pharmacological strategies in the management of type 2 diabetes (T2DM) in primary care, being the most frequent Diabetes Self- Management Education and Support (DSMES), and exercise and nutrition therapy presented the highest probability to be the best in terms of HbA1c reduction. Registration number: Our systematic review protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO) under number CRD42019127856. This research has been supported by the São Paulo Research Foundation (Grant number: 2021/07229-0).
Effectiveness of non-pharmacological strategies in primary health care for the treatment of type 2 diabetes mellitus: a systematic review and network meta-analysis
Keywords: Atençao primária; Diabetes tipo 2; Estratégias não farmacológicas; Revisão; Metanálise em rede